Non-take-up of in-work benefits: determinants, benefit erosion and indexing - Diego Muñoz-Higueras; Stephan Köppe; Rafael Granell; Amadeo Fuenmayor (Journal for Labour Market Research)
Abstract Non-take-up of welfare schemes is a key concern of policy effectiveness. Building on studies that have shown the low take-up of minimum income schemes, our case study of Ireland’s Working Family Payment is the first to analyse non-take-up of an in-work benefit and its determinants with a special focus on labour market factors. Based on EU-SILC (2014–2019) we estimate a non-take-up rate between 63 and 76%, which poses a major obstacle for effective poverty prevention. Moreover, we stress that non-take-up of in-work benefits differs to minimum income schemes. We provide new evidence on how labour market characteristics play an important role in explaining non-take-up, especially self-employment and the interaction with unemployment benefits. Benefit erosion is a key factor in declining eligibility, which should be addressed by indexing wages and prices. Furthermore, we propose policy reforms around automatic enrolment or tax credits to mitigate non-take-up and alleviate in-work poverty.